SAT0255 EVALUATION OF THE CARDIOVASCULAR INVOLVEMENT OF SYSTEMIC SCLEROSIS USING NON- INVASIVE CARDIAC IMAGING TECHNIQUES. (June 2019) - Espinet, Carina; Pizzi, Maria Nazarena; Castillo, Alfredo Guillén del; Roque, Albert; Pineda, Victor; Sanz, Isidro; Callejas-Moraga, Eduardo L.; Roca, Maria; Aguade, Santiago; Simeón-Aznar, Carmen Pilar
Abstract : Background: Systemic sclerosis (SSc) is a systemic disease that may affect many organs; among them, cardiac involvement. The prevalence of cardiac involvement in SSc varies depending on the sensitivity of the methods used for its detection. Indirect evidence suggests that subclinical cardiac involvement may eventually occur in the vast majority of patients with SSc. Early detection and monitoring of myocardial involvement are integral to SSc management, as cardiovascular involvement is known to be a poor prognostic indicator when present Objectives: To describe myocardial perfusion abnormalities and potentially associated coronary arteries lesions using non-invasive imaging techniques in a group of patients with SSc and suggestive symptoms of myocardial involvement (symptomatic) in comparison with a control group of patients with SSc without cardiac symptoms Methods: A retrospective observational study was performed including a total of 61 patients diagnosed with SSc, 52 symptomatic, with dyspnea and/or chest pain (57.98 ± 12.3 years, 45 women) and 9 asymptomatic controls (50.2±15.21 years, 8 women). All patients underwent a post-stress (treadmill or pharmacological) myocardic perfusion gated-SPECT, a cold-induced stress SPECT, that were compared to a rest SPECT (to assess ischemia and/or necrosis), as well as a cardiac CT-angiography (to asses significant coronary arteries lesions, considering stenosis of more than 50%) Results: Twenty-one out of the 52 symptomatic patients (50%) showed myocardial perfusion defects in the stress-rest SPECT: 13 (25%) showed ischemia, 13 (25%) fibrosis/necrosis, and 5 (9.6%) ischemia and necrosis. In the cold-induced SPECT, 17 patients (32.7%) had myocardial perfusion abnormalities: 10 (19.2%) showed ischemia, 13 (25%) fibrosis/necrosis and 6 (11.5%) ischemia and necrosis. In the other hand, of the 9 asymptomatic patients only 1 (11%) had ischemia and necrosis in the stress-rest SPECT, being only positive for necrosis in the cold-induced SPECT images. In the cardiac CT-angiography, 7/52 patients (13.4%) showed significant coronary lesions, 4 (57.2%) of them with perfusion defects in the SPECT images, and 3 (42.8%) without significant perfusion alterations Of the 9 asymptomatic patients, 1 (11%) had significant coronary lesions, being the same patient who presented perfusion defects in myocardial SPECT images Conclusion: The gated-SPECT is a sensitive tool for detecting myocardial perfusion alterations, normally with no associated significant coronary lesions, suggesting microvascular abnormalities. In this cohort, myocardial perfusion abnormalities were detected in 50% of symptomatic patients, whereas in only 11% of non-symptomatic patients References: [1] Fernández-Codina A, Simeón-Aznar CP2, Pinal-Fernandez I, Rodríguez-Palomares J, Pizzi MN, Hidalgo CE, Guillén-Del Castillo A, Prado-Galbarro FJ, Sarria-Santamera A, Fonollosa-Plà V, Vilardell-Tarrés M. Cardiac involvement in systemic sclerosis: differences between clinical subsets and influence on survival. Rheumatol Int. 2017 Jan;37(1):75-84. doi: 10.1007/s00296-015-3382-2. Epub 2015 Oct 25. [2] Rangarajan V, Matiasz R, Freed BH. Cardiac complications of systemic sclerosis and management: recent progress. Curr Opin Rheumatol. 2017 Nov;29(6):574-584. doi: 10.1097/BOR. Disclosure of Interests: None declared